Team Games Tournament Type Cooperative Learning Model on the Football Learning Outcomes at High School - Zulkipli Zulkipli; Hasyim Hasyim; Juhanis Juhanis (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Physical education learning, particularly in soccer material at High School 5 Pangkep, requires an innovative approach to optimize student learning outcomes that have not yet reached the maximum standard. This study aims to determine the effect of the implementation of the Teams Games Tournament (TGT) learning model on soccer learning outcomes in grade XI students at High School 5 Pangkep. This type of research is an experimental study with a quantitative approach involving a comparison between the experimental group (TGT model) and the control group (conventional model). The research sample consisted of 30 students consisting of 13 girls and 17 boys. Data was analyzed using descriptive and inferential statistics through the SPSS 27 program. The results showed that the TGT model was significantly more effective than the conventional approach in improving learning outcomes. This was evidenced by a substantial increase in the average score of the experimental group, from 67.20 in the pretest to 86.67 in the posttest, exceeding the final score of the control group of 75.27. The t-test supported this finding with a significance value of 0.001 (p < 0.05), confirming that the TGT intervention had a real impact on mastery of soccer material. This research contributes to physical education teachers in choosing varied learning strategies that can create a competitive yet fun atmosphere, while also having a positive impact on the effectiveness of learning in schools.